Iranian EFL Students’ and Teachers’ Perspectives about Computer-Assistant Language Learning (CALL) - Amini, Sima (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study examines the attitudes of both Iranian English foreign language teachers and students toward using CALL in teaching and learning English language. The purpose of this study is also going to explore a possible relationship between the students' and teachers' reported reasons for using CALL whether there is. The study was conducted at Hezareh Sevom Institute, in the Islamic Republic of Iran. This study involved one hundred forty-nine Iranian EFL students in the intermediate and advanced English language levels, and fifteen Iranian EFL teachers. Mixed research method was used to collect the data by employing students’ questionnaire and teachers ‘semi-structured interviews. The questionnaire results indicated that different browsers and operating systems were used by the Iranian EFL learners. In this study, large number of participants had their own computer which is equipped with Microsoft Windows and their preference browser was Mozilla. In addition to it, this study presents several reasons for using CALL perceived by the Iranian EFL learners. Some of these reasons are providing quick feedback, easy to use, preparing for course tests. On the other hand, reading stories, time consuming, lack of key answer, having to use the CD, direction in English and adding accent are some of the reasons participating students did not like the online materials. In response to interview questions, teachers confirmed that technology can facilitate learning English skills by providing variety of online materials for the EFL learners. Furthermore, CALL can change lecture-based classroom setting and promote the student-centered learning. On the other hand, some teachers who were above thirty-five of age expressed negative perspective about using CALL in EFL classes because of destroying hands-on activities and reducing real-world interaction among learner. By cross-checking the results gained from both EFL teachers and learners, there is a consensus noted among the reasons for which they use CALL. Keywords: Computer-assistant language learning (CALL), ELT classes, Functions of CALL, Classification of CALL

ÖZ: Bu araştırma, İranlı yabancı dil öğretmenlerinin ve öğrencilerinin Bilgisayar destekl dil eğitimi (İngilizce: Computer-assisted language learning) kullanma nedenlerini bulmayı amaçlamaktadır. Bu çalışmanın amacı, öğrencilerin ve öğretmenlerin verdiği nedenler arasında bir bağlantı olup olmadığını ortaya çıkarmaktır. Araştırma, İran İslam Cumhuriyeti Hezareh Sevom Enstitüsü'nde yapılmıştır. Ankete, orta ve ileri İngilizce dil seviyelerine sahip yüz kırk dokuz İngilizce öğretmenliği okuyan İranlı öğrenci ve on beş İranlı öğretmen katılıp veri toplamama yardım etti. Araştırmaya ait verilerin toplanması için kategorik ve Likert ölçekleri anketleri ve öğretmenler için yarı yapılandırılmış görüşmeler kullanılarak hem nicel hem de nitel yöntemler kullanıldı. Anket sonuçları, bazı belli başlı işletim sistemlerinin ve tarayıcıların İranlı EFL öğrencileri tarafından kullanıldığını gösterdi. Çok sayıda katılımcı, kendilerine ait Microsoft Windows ile donatılmış bilgisayarlarını kullandı ve kullandıkları tarayıcı Mozilla idi. Ayrıca, çalışma İranlı öğrenciler tarafından Bilgisayar destekli dil eğitimi kullanmak için algılanan çeşitli nedenler sunuyor. Bu nedenlerden bazıları hızlı geri bildirim sağlamak, kullanımı kolay, kurs sınavlarına hazırlık vb. Öte yandan bazı katılımcılar, belirtilen nedenlerden dolayı çevrimiçi materyalleri beğenmedi: hikaye okumak, zaman kaybı, cevap anahtarı eksikliği, CD kullanmak zorunda kalmak, İngilizce açıklamalar ve aksan eklenmesi. Anket sorularına cevap olarak, öğretmenler teknolojinin yabancı dil okuyan öğrenciler için çeşitli çevrimiçi materyaller sunarak İngilizce öğrenmeyi kolaylaştırabileceğini doğruladılar. Ayrıca, Bilgisayar destekli dil eğitimi geleneksel sınıf ortamını değiştirebilir ve öğrenci merkezli öğrenmeyi teşvik edebilir. Öte yandan, otuz beş yaşın üzerindeki öğretmenler, uygulamalı etkinlikleri yok ettiği ve öğrenciler arasında gerçek dünyayla etkileşimi azalttığı için, Bilgisayar destekli dil eğitime olumsuz baktıklarını ifade etmişlerdir.Yabancı dil öğrencilerinden ve öğretmenlerinden elde edilen sonuçlar çapraz kontrol edilerek, bilgisayar destekli dil eğitim kullanma nedenleri arasında bir fikir birliği olduğu sonucuna ulaşılmışır. Anahtar Kelimeler: Bilgisayar destekli dil eğitimi, ELT sınıfları, Bilgisayar destekli dil eğitiminin işlevleri, Bilgisayar destekli dil eğitiminin sınıflandırılması
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2019. Supervisor: Assoc. Prof. Dr. İlkay Gilanlıoğlu.
Keywords: English Language Teaching (ELT); English Language--Study and Teaching (Higher); Language of Instruction--Second Language Learning--Computer Assistant Language LEarning--Students Perceptions; Computer-assistant language learning (CALL); ELT classes; Functions of CALL; Classification of CALL